Impact of office tenants’ electricity use on the cost-optimal solutions in a cold climate - Kuivjõgi Helena; Laas Liina; Ferrantelli Andrea; Thalfeldt Martin (E3S Web of Conferences, 2021)
The buildings’ energy performance requirements in Estonia are based on cost-optimality analysis according to the EPBD and pre-defined building performance simulation (BPS) input data from EN 16798-1:2019. Previous studies have shown that the real electricity use of office building tenants differs from the currently used input data in BPS in Estonia – less in total energy use, but more in the shape of the profiles. The aim of this work is to investigate what is the impact of these differences on the cost-optimal solutions, which are identified based on BPS and the self-consumption of the photovoltaic panel (PV) systems. This study describes the energy performance and construction cost analysis of a new office building in Tallinn, Estonia. BPS based on the EN 16798-1 and a model derived from measurements in a real building were conducted and cost-optimal building solutions identified. The variables were building envelope insulation thickness, air handling unit size and effectiveness, electrical lighting control principles and PV system nominal power. The calculated energy use of the building with the two different sets of input data differed significantly. However, the set of cost-optimal solutions identified with EN 16798-1:2019 input data had minor differences from the set of solutions identified with the more realistic model. The decrease of net present value over 20-year period for cost-optimal solution was 11-14 €/m2 compared to the designed building.The realistic office tenants’ electricity model increased the calculated self-consumption of the PV system from 95% to 100%.